Health Education Using Booklet Improve Knowledge of Type II Diabetes Mellitus Patients in Mataram City, Indonesia - Cembun, Cembun; Fathoni, Akhmad; Nadirah, Nurul (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2025)
Hypoglycemia and hyperglechemia are frightening, dangerous, and potentially life-threatening for patients with diabetes. Nurses can act proactively and change the way care is provided. It is therefore necessary to develop safe and effective ways to proactively manage diabetes and hyperglycemia both in hospital and at home. One of the most important nursing actions to take is the provision of health education to patients. This study aims to identify the influence of health education using booklet in the knowledge of patients with type 2 diabetes mellitus. This study uses a quantitative approach with a pre-experimental research design of one group pre-posttest design. The sample in this study was 32 respondents selected from the population of type 2 DM patients in Karang Pule Health Center. The instrument used was the DKQ-24 (Diabetes Knowledge Questionnaire). Data on were analyzed using Wilcoxon test. The results showed that there was a difference in the average score between knowledge before and after health education (P = 0.000; p<0.05). The results of the study show that there is an influence of health education using booklet on the level of knowledge. This study signifies the role of nurses and the need of appropriate media such as booklet to educate patients with type 2 DM and increase their knowledge in managing stable blood glucose and preventing complications.